Dependence of secondary operations in powder metallurgy and their impact on the electrical conductivity of MWCNTs/Cu nanocomposites. (2022) - Mahesh,; Singh, Kalyan Kumar; Koti, Vishwanath; Rawat, Prashant
Abstract: This study reports the electrical conductivity of multi-wall carbon nanotubes (MWCNTs) embedded copper nanocomposites. Copper-based nanocomposites are prepared by the powder metallurgy route method with two different secondary operations, (i) hot pressing and (ii) rolling. The MWCNTs doping weight percentage used are 0, 0.25, 0.5, 0.75 and 1 wt% of copper (or base material). The four-point probe technique is used to measure the electrical resistance of the prepared samples. The experimental results showed that MWCNTs reinforcement increased the electrical resistance of the copper. Moreover, the rolled MWCNTs/Cu nanocomposites resulted in lower electrical resistance than the hot pressed MWCNTs/Cu nanocomposites.